1998
DOI: 10.1111/j.1475-6811.1998.tb00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Dependency and insecurity in romantic relationships: Development and validation of two companion scales

Abstract: This article presents self‐report scales for the assessment of perceived dependency and insecurity in a romantic relationship. These scales were originally developed many years ago (Fei & Berscheid, 1977) but were never published. The process of original scale development is summarized, and results from five studies (total N= 1,283; including data from the original Fei & Berscheid studies) are presented showing evidence for (a) scale reliability and validity; (b) the association between dependency and insecuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Typically, dependence and commitment are considered to be positive and important aspects of relationship stability. Relationship dependence leads to greater commitment over time (Attridge, Berscheid, & Sprecher, 1998;Wieselquist, Rusbult, Foster, & Agnew, 1999).…”
Section: Chapter 4 Settling For Less: Relationship Dependencementioning
confidence: 99%
“…Typically, dependence and commitment are considered to be positive and important aspects of relationship stability. Relationship dependence leads to greater commitment over time (Attridge, Berscheid, & Sprecher, 1998;Wieselquist, Rusbult, Foster, & Agnew, 1999).…”
Section: Chapter 4 Settling For Less: Relationship Dependencementioning
confidence: 99%
“…Such linkage stimulates a sense of dependency on the object of their affection. Dependency is defined as the perception that only a particular person or relationship can satisfy the individual's needs, thus relying solely on that specific source for fulfillment (Attridge et al 1998;Rusbult et al 1998). Such beliefs are typical of those stalkers studied clinically (Meloy 1998;Mullen et al 2000).…”
Section: Goal Linkagementioning
confidence: 99%
“…shown that dependence leads individuals to experience anxiety about either the continued satisfaction of needs (Bersheid and Fei, 1977;Attridge et al, 1998) or the effects of possible future abandonment (Davilla and Bradbury, 2001). In one test of these ideas in joint ventures, it was found that increased dependence had a negative effect on both organisations' feelings of security (Robson et al, 2006).…”
Section: Supplier Dependence Aversionmentioning
confidence: 99%